Capacity gain of beamforming techniques in a WCDMA system under channelization code constraints. - Ramiro-Moreno, J.
This study addresses the performance of a wideband code-division multiple-access mobile communications system with beamforming antenna arrays (AAs) at the base station, synthesizing a grid of beams. In order to fully exploit the capacity gain from beamforming without jeopardizing the stability of the system, a directional power-based admission control (AC) scheme is applied. Due to the higher capacity offered by beamforming techniques, shortage of orthogonal channelization codes in the downlink becomes an increasingly important factor, which may result in blocking of users before the interference power limit is reached. The problem of channelization code shortage is addressed, and a solution based on splitting the cell into several code regions is proposed. For a network with circuit switched data services operated at 64 kb/s, the capacity gain for an eight-element AA is found to equal a factor of 2.5 for a universal mobile telecommunications equivalent system, with one channelization code set per cell. The capacity gain is limited by severe channelization code shortage under these circumstances. This problem is solved by deploying a cell splitting strategy with multiple code regions, which subsequently results in a capacity gain increase to a factor of 3.4. Furthermore, the soft capacity mechanism associated with partial deployment of AAs in a subset of the cells in the network is also addressed. It is demonstrated that a hot spot cell with AAs also helps increase the capacity of the surrounding cells with conventional sector antennas when using a power-based AC strategy.
Keywords: WCDMA system; Admission control scheme; Antenna arrays; Base station; Beamforming techniques; Capacity gain; Cell splitting strategy; Code blocking probability; Mobile communication systems; Orthogonal channelization code constraints; Packet traffic; Wideband code division multiple access